Kontribusi Galeri Investasi Syariah FEBI IAIN Kediri dalam Mengakselerasi Literasi Keuangan Digital Mahasiswa - Aulya Purwitasari; Mochamad Ali Muchtar; Suhartini Suhartini; Andriani Andriani; Naning Fatmawatie (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Sharia financial literacy in accordance with Islamic principles is still considered low among society, especially among the younger generation, including students. The level of sharia financial literacy in Indonesia only reaches 8.93% of the total population, far below conventional financial literacy which reaches 38.03%. This shows that the awareness and understanding of Indonesian society is still very limited. The research method in this journal consists of three main stages. The first stage is data search, which is carried out to understand the conditions and problems faced by GIS administrators. The second stage is problem analysis, where the collected data is analyzed systematically using qualitative methods. Next, there is the discussion stage to resolve the problem, this is done together with the GIS administrator. The FEBI IAIN Kediri Sharia Investment Gallery (GIS) was founded in response to the need to increase student financial literacy, especially in the context of sharia investment. GIS functions as a digital financial education center, providing training, seminars and workshops to increase understanding of sharia-based financial technology. GIS not only focuses on theory, but also provides practical experience to students through investment simulation programs. Running of GIS Febi IAIN Kediri. Kediri, at this early stage, has contributed to increasing digital financial literacy among students through increasing understanding of sharia financial products, getting used to the use of financial technology, increasing awareness of digital security, and integrating sharia principles with technology.